Iron deficiency is associated with reduced levels of Plasmodium falciparum-specific antibodies in African children - Bundi, CK; Nalwoga, A; Lubyayi, L; Muriuki, J; Mogire, R; Opi, H; Mentzer, AJ; Mugyenyi, CK; Mwacharo, J; Webb, EL; Bejon, P; Williams, TN; et al. (Oxford University Press, 2020)
Background: Iron deficiency (ID) and malaria are common causes of ill-health and disability among children living in sub-Saharan Africa. Although iron is critical for the acquisition of humoral immunity, little is known about the effects of ID on antibody responses to Plasmodium falciparum malaria.